“What’s on the Interface Tonight?”: A longitudinal analysis of the publishing strategies of public service video-on-demand platforms in the UK and Denmark - Kelly, JP; Sørensen, Jannick Kirk (MedieKultur: Journal of media and communication research, 2021)
This article presents a new method for analysing video-on-demand (VOD) publishing strategies over time. It demonstrates this method on two public service media [PSM] VOD platforms from two countries: BBC iPlayer in the UK and DRTV in Denmark. The article begins with a close analysis of their respective interfaces to contextualise our subsequent “distant reading” (Moretti, 2013) of these platforms. We use distant reading to examine the spatial and temporal patterns present in both interfaces, with our analysis based on two original data sets that have been compiled over a period of approximately 14 months (beginning in August 2019). This data is analysed and visualised in order to reveal patterns and anomalies at a macroscopic level. Through a close and distant reading of these services, we offer valuable new insights into, and metrics for, the performance and publishing strategies of PSM VOD platforms.